Family Functional Their Related Factor for Stunting: A Cross Sectional Study of Agrarian Families - Sulton Wariin; Tantut Susanto; Iis Rahmawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2025)
Stunting is a problem for families, especially for those who work in agriculture. Families can reduce the risk of stunting by optimizing their functions for the common welfare. This research aims to analyze differences in the function of agricultural families regarding the incidence of stunting. This research is a cross-sectional study involving 236 agrarian families with stunted children using stratified random sampling in two stunting locus areas and one other area in the Jember Regency. Family functioning was measured using the Family Assessment Device Questionnaire, and stunting was calculated using WHO Anthroplus. Data were analyzed using descriptive and comparative analysis with Mann Whitney test. The results showed a significant influence of family function on problem-solving (0.001), communication (0.001), roles (0.001), affective responsiveness (0.001). Malfunctioning family functions can contribute to the incidence of stunting. It is hoped that families will be able to improve family function for the welfare of all family members with the contribution of community nurses through visits and counseling with a family approach